Relationship between body image perception and stress towards eating behaviour among IIUM students - Selamat, Ain Salsabila; Ibrahim, Muhamad Ariff; Mohd Nazori, Mohd Nazir; Saad, Nurulwahida; Waisulqrnai, Siti Adibah (International Islamic University Malaysia, 2024)
Background: University students, facing academic and personal challenges, often experience stress that can worsen body image concerns, leading to unhealthy eating patterns like overeating, restrictive eating, or disordered eating. Therefore, the main objective of this research is to assess the relationship between body image perception and stress towards eating behaviour among students at the International Islamic University Malaysia (IIUM). Methods: The study used a cross-sectional design, in which samples were obtained using a convenient sampling, with a total of 384 students. Data was collected using the Perceived Stress Scale (PSS), the Body Image Scale for Youth (BISY), and the Dutch Eating Behaviour Questionnaire (DEBQ). Results: Stress is significantly associated with emotional eating (r = 0.142, p < 0.01). Body image perception also showed a significant relationship with restraint (r = 0.301, p < 0.01), emotional (r = 0.197, p < 0.01), and external eating behaviours (r = 0.155, p < 0.01). Cultural values (r = 0.167, p < 0.01) and social support (r = 0.122, p < 0.01) weakly correlate with external eating. Negative associations exist between body evaluation and both restraint (r = -0.129, p < 0.05) and emotional eating (r = -0.122, p < 0.05). Health and spirituality priorities negatively related to restraint (r = -0.186, p < 0.01) and emotional eating (r = -0.144, p < 0.01). Multiple regression analysis showed dimension body image perception (emotion and behaviour) predicts restraint and emotional eating behaviour. Results also showed that dimension emotion and behaviour, perceived social support and perceived cultural values are significant predictors of external eating behaviour. Conclusion: These findings underscore the complex interplay between stress, body image perception, and eating behaviours among IIUM students, highlighting the need for comprehensive support systems to address these interrelated issues.